Pengaruh Komposisi Ekstrak Mengkudu (Morinda citrifilia L.) Sebagai Antibakteri Pada Shampo Herbal Berbasis Methyl Ester Sulfonat (MES) - Syafira Dara; Suryati Suryati; Meriatna Meriatna; Nasrul ZA (LPPM Universitas Malikussaleh, 2021)
Shampoo is a preparation that contains surfactants in a suitable form and is useful for removing dirt and grease attached to the hair and scalp so as not to harm the hair and scalp. In this study the ingredients used were noni fruit extracts and surfactants using Methyl Ester Sulfonate (MES). The purpose of this study was to analyze the effect of time when making herbal shampoo, the effect of adding noni fruit extract to the quality of shampoo. To obtain the noni fruit extract maceration process is used by using distilled water. Noni ripe fruit is cut and then blended and then added 2 liters of aquadest, evaporated in a rotary evaporator. The processing of herbal shampoo is done by the influence of the volume of noni fruit extract and time by comparison: 5 ml: (1,2,3,4) minutes, 10 ml: (1,2,3,4) minutes, 15 ml: (1, 2,3,4) minutes, 20 ml (1,2,3,4) minutes. Tests carried out pH testing, foam stability test (%), foam height test (cm), viscosity (cps) and anti-bacterial test (colony, cm2). Based on the research results obtained high foam with 88 mm, foam stability 92.04%, Viscosity 2.31, antibacterial 31.7 colonies / cm2, and pH 4.2. The research results are expected to meet Indonesian National Standards.